CellShape: A user‐friendly image analysis tool for quantitative visualization of bacterial cell factories inside - Goñi‐Moreno, Ángel; Kim, Juhyun; de Lorenzo, Víctor (Biotechnology journal, 2017)
Visualization of the intracellular constituents of individual bacteria while performing as live biocatalysts is in principle doable through more or less sophisticated fluorescence microscopy. Unfortunately, rigorous quantitation of the wealth of data embodied in the resulting images requires bioinformatic tools that are not widely extended within the community‐let alone that they are often subject to licensing that impedes software reuse. In this context we have developed CellShape, a user‐friendly platform for image analysis with subpixel precision and double‐threshold segmentation system for quantification of fluorescent signals stemming from single‐cells. CellShape is entirely coded in Python, a free, open‐source programming language with widespread community support. For a developer, CellShape enhances extensibility (ease of software improvements) by acting as an interface to access and use existing Python modules; for an end‐user, CellShape presents standalone executable files ready to open without installation. We have adopted this platform to analyse with an unprecedented detail the tridimensional distribution of the constituents of the gene expression flow (DNA, RNA polymerase, mRNA and ribosomal proteins) in individual cells of the industrial platform strain Pseudomonas putida KT2440. While the CellShape first release version (v0.8) is readily operational, users and/or developers are enabled to expand the platform further. The CellShape tool allows translation of fluo‐rescence microcopy observations of single bacteria into a quantitative description of the inside constituents of the cell